Response surface optimization of biodiesel synthesis from crude palm oil (CPO) using CaO/silica gel heterogeneous catalyst based on blood cockle shell and coconut fiber - Nurhayati, Nurhayati; Awaluddin, Amir; Mulyani, Yenni (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study successfully synthesized a hybrid catalyst CaO-silica gel from environmentally friendly raw materials, CaO derived from blood clam shells and silica gel obtained from coconut fiber waste ash. The catalytic activity was evaluated in the synthesis of biodiesel from crude palm oil (CPO). The CaO-Silica gel catalyst was synthesized by the wet impregnation method with variations of silica gel, namely 5, 10 and 15 wt%. The catalyst was characterized using XRD, XRF, SEM, and BET analysis. The results showed a decrease in CaO content with increasing silica gel concentration, while XRD analysis confirmed the presence of lime, portlandite, Ca₂SiO₄, and silica oxide minerals. The addition of silica gel reduced the crystal size and crystallinity and increased the surface area of the catalyst. Optimization of biodiesel production was carried out using the Response Surface Methodology (RSM), considering variables such as temperature, reaction time, molar ratio of oil to methanol, and catalyst loading. The highest biodiesel yield was obtained using 5% CaO/silica gel catalyst at a temperature of 65°C, a reaction time of 60 minutes, an oil-methanol molar ratio of 1:9, and a catalyst addition of 2%, resulting in a biodiesel yield of 99.52%. In addition, the methyl ester content reached 99.21% using a 10% CaO/silica gel catalyst. The resulting biodiesel met ASTM and EN standards, except for the acid value.